2017
DOI: 10.1080/21645515.2017.1362514
|View full text |Cite
|
Sign up to set email alerts
|

Soluble F proteins exacerbate pulmonary histopathology after vaccination upon respiratory syncytial virus challenge but not when presented on virus-like particles

Abstract: Respiratory syncytial virus (RSV) fusion (F) protein is suggested to be a protective vaccine target although its efficacy and safety concerns remain not well understood. We investigated immunogenicity, efficacy, and safety of F proteins in a soluble form or on virus-like particle (F-VLP). F VLP preferentially elicited IgG2a antibody and T helper type 1 (Th1) immune responses whereas F protein induced IgG1 isotype and Th2 responses. Despite lung viral clearance after prime or prime-boost and then RSV challenge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…4C ). Previous studies have reported no detection or low levels of eosinophil infiltration in RSV infected naïve animals and in less severe human patients ( 11 12 20 23 ). In consistent, we observed no eosinophils or below the detection limit in the lung from WT and CD4KO mice without FI-RSV vaccination after challenge with RSV ( Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…4C ). Previous studies have reported no detection or low levels of eosinophil infiltration in RSV infected naïve animals and in less severe human patients ( 11 12 20 23 ). In consistent, we observed no eosinophils or below the detection limit in the lung from WT and CD4KO mice without FI-RSV vaccination after challenge with RSV ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The fixed lung samples were processed and then embedded paraffin blocks for tissue sections. Lung tissue sections with a thickness of 5 μm were stained with H&E or hematoxylin and Congo red (H&CR) to evaluate lung histopathologic changes and eosinophil infiltration, respectively as previously described ( 13 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…After processing, the tissues were embedded in paraffin and sectioned of 5 µm to stain with hematoxylin and eosin (H&E). Lung histopathology after H&E staining was blind scored in the area of airways, blood vessels, and interstitial spaces with scales of 0 to 3 (0: none, 1: mild, 2: moderate, 3: severe), as detailed in previous studies [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, prime immunization of mice with RSV F VLP vaccine induced Th1biased immune response, preventing the induction of lung histopathology due to subsequent FI-RSV vaccination [114]. Unique immunogenic properties of RSV F VLP platforms were evident by a study reporting that soluble F protein vaccination exacerbated pulmonary histopathology upon RSV challenge but not when presented on VLPs in a mouse model [115]. Most individuals are considered to be infected with RSV by ages two to three years old but live RSV infection did not provide long-term protective immunity.…”
Section: Vaccine Efficacy Of Rsv Vlp Vaccinesmentioning
confidence: 99%